Reaction of adult rats' erythrocytes under gingivitis during respiratory hypoxia - V. F. Cheremisina (Kazimierz Wielki University, 2017)
Cheremisina V. F. Reaction of adult rats' erythrocytes under gingivitis during respiratory hypoxia. Journal of Education, Health and Sport. 2017;7(1):468-477. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.321677 http://ojs.ukw.edu.pl/index.php/johs/article/view/4284         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2017; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.01.2017. Revised 16.01.2017. Accepted: 24.01.2017.   REACTION OF ADULT RATS' ERYTHROCYTES UNDER GINGIVITIS DURING RESPIRATORY HYPOXIA   V. F. Cheremisina   National University of Pharmacy, Kharkiv, Ukraine cheremishav@mail.ru   Abstract The article presented results of the investigation of reactions erythrocytes under gingivitis of adult rats with respiratory hypoxia. Studied such factors as changes in the dynamics of hemoglobin, erythrocytes count and hematocrit. Under gingivitis during respiratory normobaric hypoxia develops oxidative stress and increased generation of ROS. Changes in the number of red blood cells, hemoglobin and red blood cell indices with gingivitis by hypoxia caused to membranes destruction processes in red blood cells, a decrease in their absolute numbers due to hemolysis; changes of hematocrit due of redistribution the blood. Keywords: hypoxia, erythrocytes, gingivitis, hemoglobin, hematocrit.